EXPORT TRADE AND THE SRI LANKAN ECONOMY INQUIRY INTO THE ISSUE OF EXPORT INSTABILITY - Athukoralage, Premachandra (My University, 2016)
Attached

This study is an empirical examination of the causes and economic implications of export instability in the context of the economy of Sri Lanka. The study has eight chapters. The first three chapters provide the framework for the ensuring analysis. Chapter 1 outlines the purpose and scope of the study. Chapter 2 reviews the literature. The main structural relationships of the Sri Lankan economy are examined in Chapter 3, in order to identify the key expert linkages. Chapter 4 and 5 analyse causes of export instability. In Chapter 4, the changing pattern of the export structure during the period 1950-79 is studied in order to shed light on the relationship between geographical and commodity concentration and the degree of export instability. The relative contribution of each commodity/commodity group and each market outlet to the instability in total export earnings is also examined. The findings provide little empirical support for the hypothesis that export instability is caused by geographical and commodity concentration. Chapter 5 investigates the contributions of price and volume variations and supply and demand shifts to instability in export earnings derived from the major export commodities. It is found that for the most part instability is attributable to variations in prices which are caused by shifts in foreign demand. Chapter 6 is concerned with the impact of export instability. First, an econometric model is constructed for the period 1959-77 to capture the salient features of the export dependence of the economy. Second, the model is simulated in a regime of constant annual export growth and the resultant changes in the degree of instability and annual growth rate of each key macro variable are examined. The results suggest that export instability has and adverse impact on the domestic economy, especially as it relates to developmental imports, capital formation and government revenue. International remedial measures and their relevance for Sri Lanka are discussed in Chapter 7. The chapter suggests that to date progress in the implementation of the proposed in Integrated Program for Commodities (IPC) leaves no room for optimism. The effectiveness of the compensatory financing facility (CFF) of the IMF is found to have been constrained by quota-related borrowing limits and rigid repayment conditions. The study concludes in Chapter 8 that in the long-run Sri Lanka’s success in achieving accelerated and sustained growth, while making the economy more resilient to export instability, lies in a concerted and unified development strategy aimed at establishing a wider base of export earnings, promoting domestic agriculture and restructuring the industrial sector to lessen its undue reliance on traditional exports for imported inputs.